Pembinaan Pemuda Kristen Milenial pada Era Artificial Intelligence di Sekolah Tinggi Teologi Mawar Saron Lampung - Hasibuan, Serepina Yoshika; Larosa, Setiaman; Marbun, Saedo; Walean, Rudy Roberto; Jhoni, Jhoni; Pratama, Andrean Hangga; Kati, Dida Hae; Nael, Yonathan Natan (Sekolah Tinggi Teologi Real Batam, 2024)
Technology cannot be stopped from progressing from time to time. In the course of its development. Artificial Intelligence is one of the advances in technology that currently dominates human life. Artificial Intelligence or what is known as Artificial Intelligence (AI) is widely used by computer devices for automated programming, such as the Google platform, drones, smart cars and so on. With the convenience provided by this AI service, it makes human work easier. However, AI has a negative influence if it is not used wisely. This can be seen from the performance of the AI system with data accuracy and satisfactory work results as well as efficient and very short time. On the other hand, there is an opinion that AI will make humans lazy because the work they do has been taken over by AI, and will result in a lower quality of human work. Human activities will be replaced by devices that use AI systems and will result in unemployment. Therefore, in this PKM activity it is very important for the millennial generation in the era of Artificial Intelligence to be given guidance and introduction to AI so that it can be used and provide good benefits, especially in terms of following its developments in accordance with the practice of their Christian faith. Based on the evaluation results, PKM activities have positive benefits in developing the spirituality of Christian youth in the AI era. Keywords: technology; christian youth development; artificial intelligence AbstrakTeknologi tidak dapat dibendungi kemajuannya dari masa ke masa. Dalam perjalanan perkembangannya. Artificial Intelligence merupakan salah satu kemajuan di bidang teknologi yang saat ini menguasai kehidupan manusia. Artificial Intelligence atau yang dikenal dengan Kecerdasan Buatan (AI) banyak digunakan oleh perangkat-perangkat komputer guna pemrograman yang otomatisasi, seperti platform google, drone, mobil pintar dan sebagainya. Dengan kemudahan yang diberikan oleh layanan AI ini, membuat pekerjaan manusia lebih mudah. Namun, AI nemberikan pengaruh negatif apabila tidak digunakan dengan bijak. Hal ini telihat bagaimana kinerja yang dilakukan oleh sistem AI dengan keakuratan data dan hasil kerja yang memuaskan serta waktu yang efisien dan sangat singkat. Di sisi lain, ada anggapan bahwa AI akan membuat manusia bermalas-malasan karena perkerjaan yang dilakukan telah diambil alih oleh AI, serta akan mengakibatkan rendahnya kualitas kerja manusia. Kegiatan manusia akan digantikan oleh perangkat yang menggunakan sistem AI dan akan mengakibatkan pengangguran. Oleh sebab itu, dalam kegiatan PKM ini sangat penting bagi generasi milenial di era Artifical Intelligence untuk diberikan pembinaan dan pengenalan AI agar dapat digunakan dan memberikan manfaat yang baik, terkhusus dalam hal mengikuti perkembangannya sesuai dengan pengamalan iman Kristennya. Berdasarkan hasil evaluasi, kegiatan PKM bermanfaat positif dalam membina kerohanian pemuda Kristen di era AI.Kata Kunci: teknologi; pembinaan pemuda kristen; arificial intelligence